PELATIHAN PERENCANAAN KEUANGAN : INDAHNYA MASA PENSIUN - Sri Mendari, Anastasia; Suci Kewal, Suramaya; Andri Putranto, Yohanes; Heriyanto, Heriyanto; Widyartono, Agustinus (Universitas katolik Musi Charitas, 2020)
Community Service activities are carried out in collaboration with the Palembang Archdiocese's1st Dean Family Commission, who entrusted this material to a team of lecturers from the Facultyof Business and Accounting, Musi Charitas Catholic University Palembang. The method ofproviding material in the form of lectures, videos, simulations and exercises. Participants who takepart in this activity are those who plan in the near future to carry out Catholic marriages. Thenumber of participants was 65 people, followed by 49% men and 51% women, most of theparticipants had an undergraduate degree (66%), with ages ranging from 23-27 years (74%), withincome levels ranging from 2-4 million (45% ). Providing material on